Edukasi dan Literasi Keuangan Kepada Kelompok Masyarakat tentang Investasi Ilegal di Era Digital - Daud, Muhammad; Armia, Yasser; Hakim, Lukman; Aziz, Daska (Unity Academy, 2024)
Illegal investment is a serious threat to the financial stability of society, especially in the increasingly complex digital era. The lack of financial education and literacy and the high temptation of large returns often make people victims of illegal investment. This article aims to educate the public in recognizing the characteristics of illegal investment and steps to avoid it as well to prevent illegal investment. The methods applied are by conducting community-based education and counseling, disseminating information through social media, and simulating real cases as a learning tool. This financial education and literacy were implemented in community groups, moms, and youth groups as 50 participants. The results of the education showed an increase in participants' understanding of the characteristics of illegal investment, such as promises of unreasonable profits, lack of legality, and minimal transparency. In addition as 80% of participants admitted to being more confident in evaluating investment after participating in this financial education and literacy, while 75% of participants stated that they were able to prepare wiser financial plans. These findings confirm that proper financial education and literacy can be an effective preventive measure in preventing losses due to fictitious investments, while supporting the creation of sustainable financial security at the individual and community. The conclusion of financial education and literacy illegal investments shows that comprehensive and interactive education can effectively and prevent of fictitious investments. Continuous financial education and literacy are very important to support the financial security and create a community that is more aware of investments.